Answer:
x = 3 1/2
Step-by-step explanation:
You could simplify the given equation first, then solve the resulting 2-step linear equation. It might work better to undo the operations done to the variable.
<h3>Solution</h3>
(5 1/6 -x)(2.7) -5 3/4 = -1 1/4 . . . . . given
(5 1/6) -x)(2.7) = 4 1/2 . . . . . . . add 5 3/4 to both sides
(5 1/6 -x) = 4.5/2.7 = 5/3 . . . divide by 2.7
31/6 -10/6 = x . . . . . . . . . . add x-5/3, use common denominators
21/6 = x = 7/2
x = 3 1/2
Just a moment while I review this
9514 1404 393
Answer:
C) No, Kayla is not correct, because the remainder is -49 not 149
Step-by-step explanation:
The remainder from division by x+5 can be found by evaluating the polynomial at x=-5, the value of x that makes the divisor zero.
Evaluation is often easier when the function is written in Horner form.
((x +2)x -4)x +6
For x=-5, this is ...
((-5 +2)(-5) -4)(-5) +6 = (-3(-5) -4)(-5) +6 = 11(-5) +6 = -49
Kayla is not correct; the remainder is -49.